Building Performance Excellence through HR Innovation: The Role of Competence and Compensation in the Education Sector - Abdulah Aulia Mulky Madani; Asep Jamaludin; Nandang Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
Teacher performance plays a crucial role in the success of the learning process. Competence and appropriate compensation are often identified as key factors influencing performance outcomes. This study aims to examine the effects of competence and compensation on teacher performance at State Senior High School 1 Tempuran, Karawang, both individually and collectively. Utilizing a quantitative approach, all teachers at the school were included as research participants. The findings reveal that competence has a significant individual impact on teacher performance, while compensation does not show a meaningful influence when considered separately. However, when analyzed together, competence and compensation collectively contribute to teacher performance. These results highlight the importance of enhancing professional competence as a strategy to improve overall teaching quality, with compensation playing a supportive role.